Increasing the Role of the Neighborhood In Society is a Difficult Task (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Neighborhood has been important in our life since time immemorial, it has been a place of peace, harmony and solidarity, enlightenment and education. Moreover, the neighborhood is our long past, present, and future. It is this ring that provides the basis for the continuity of our life.